Novel frameshift variants expand the map of the genetic defects in IRF2BP2 - García-Aznar, José María; Maneiro Pampín, Emilia; García Ramos, Maite; Acuña Pérez, María José; Paz Gandiaga, Nerea; Minguell Domingo, Laura; Calavia, Olga; Soler-Palacin, Pere; Colobran, Roger; Novoa Bolívar, Erika M.; Ocejo Vinyals, Javier Gonzalo (Frontiers in Immunology, 2023)
Background: At present, the knowledge about disease-causing mutations in IRF2BP2 is very limited because only a few patients affected by this condition have been reported. As previous studies have described, the haploinsufficiency of this interferon transcriptional corepressors leads to the development of CVID. Very recently, a more accurate phenotype produced by truncating variants in this gene has been defined, manifesting CVID with gastrointestinal inflammatory symptoms and autoimmune manifestations.We analyzed 5 index cases with suspected primary immunodeficiency by high throughput sequencing. They were submitted for a genetic test with a panel of genes associated with immune system diseases, including IRF2BP2. The screening of SNVs, indels and CNVs fulfilling the criteria with very low allelic frequency and high protein impact, revealed five novel variants in IRF2BP2. In addition, we isolated both wild-type and mutated allele of the cDNA from one of the families.2 This is a provisional file, not the final typeset article Results: In this study, we report five novel loss-of-function (LoF) mutations in IRF2BP2 that likely cause primary immunodeficiency, with CVID as more frequent phenotype, variable expression of inflammatory gastrointestinal features, and one patient with predisposition of viral infection. All identified variants were frameshift changes, and one of them was a large deletion located on chromosome 1q42, which includes the whole sequence of IRF2BP2, among other genes. Both de novo and dominant modes of inheritance were observed in the families here presented, as well as incomplete penetrance.We describe novel variants in a delimited low-complex region, which may be considered a hotspot in IRF2BP2. Moreover, this is the first time that a large CNV in IRF2BP2 has been reported to cause CVID. The distinct mechanisms than LoF in IRF2BP2 could cause different phenotype compared with the mainly described. Further investigations are necessary to comprehend the regulatory mechanisms of IRF2BP2, which could be under variable expression of the disease.